Prevalence and long-term prognosis of patients with 'narrower than normal' QRS complexes. Issue 4 (14th January 2017) - Maury, Philippe; Lematte, Elodie; Derval, Nicolas; Rollin, Anne; Bongard, Vanina; Duparc, Alexandre; Mondoly, Pierre; Cardin, Christelle; Sadron, Marie; Galinier, Michel; Carrié, Didier; Hocini, Meleze; et al.
Abstract: Aims: Very narrow QRS have been reported in sudden death survivors but prevalence and prognosis role of narrow QRS is unknown. Methods and results: 546 healthy men between 50 and 60 years (group 1) and 373 similar patients with coronary artery disease (368 men, group 2) underwent signal averaged ECG (SA-ECG) allowing precise measurement of QRS duration. All cause-mortality was determined after 18 ± 3 years follow-up. Mean QRS duration was 97 ± 13 ms in group 1 and 103 ± 16 ms in group 2. Tenth percentile was 84 ms in group 1 and 85 ms in group 2. All cause-mortality in group 1 was 10.4% (57/546): 6/85 in case of QRS <85 ms (7%) and 2/23 (9%) in case of QRS >120 ms (ns). HR for all-cause mortality was 0.75 (95% CI 0.32–1.76, P = 0.52) for QRS <85 ms and 0.86 (95% CI 0.21–3.53, P = 0.84) for QRS >120 ms. All cause mortality in group 2 was 29% (109/373): 7/44 in case of QRS <85 ms (16%) and 22/44 (50%) in case of QRS >120 ms ( P = 0.002). HR for all-cause mortality was 0.65 (95% CI 0.29–1.45, P = 0.29) for QRS <85 ms and 1.73 (95% CI 1.02–2.94, P = 0.05) for QRS >120 ms. Conclusion: QRS duration <80–85 ms can be observed in a significant proportion of middle-aged healthy males and in similar patients with ischemic heart disease. Narrow QRS were not linked to prognosis in any group.